2000
DOI: 10.1111/j.8755-8920.2000.430106.x
|View full text |Cite
|
Sign up to set email alerts
|

Activated Protein C Resistance and Factor V Leiden Mutation can be Associated with First‐ as well as Second‐Trimester Recurrent Pregnancy Loss1

Abstract: APCR and factor V Leiden are associated with unexplained recurrent pregnancy loss. The occurrence of APCR and factor V Leiden seems to be linked to post-embryonic first-trimester as well as second-trimester recurrent pregnancy loss. The significance of acquired, non-heritable APCR in recurrent fetal loss patients, especially in the second-trimester aborters, is still to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 15 publications
5
89
0
4
Order By: Relevance
“…Grandone et al (1997) reported a 31.2% prevalence of factor V Leiden in women with second trimester fetal losses compared to 4.2 % in matched controls. These findings were further supported by Younis et al (2000) who described a significantly higher incidence of factor V Leiden in women with first trimester and second trimester losses compared to a control group; 16%; 22% and 6% respectively. Reznikoff-Etievant et al (2001) also found a higher incidence of factor V Leiden; 10.38% (27/260) compared to a control group (4.7 % (11/240)).…”
Section: Hereditary Apcr (Factor V Leiden) and Pregnancy Losssupporting
confidence: 56%
See 1 more Smart Citation
“…Grandone et al (1997) reported a 31.2% prevalence of factor V Leiden in women with second trimester fetal losses compared to 4.2 % in matched controls. These findings were further supported by Younis et al (2000) who described a significantly higher incidence of factor V Leiden in women with first trimester and second trimester losses compared to a control group; 16%; 22% and 6% respectively. Reznikoff-Etievant et al (2001) also found a higher incidence of factor V Leiden; 10.38% (27/260) compared to a control group (4.7 % (11/240)).…”
Section: Hereditary Apcr (Factor V Leiden) and Pregnancy Losssupporting
confidence: 56%
“…However, in those studies that do address this, none of them dispute the definite association between acquired APCR and recurrent pregnancy loss. Younis et al (2000) were intrigued with their finding of a higher prevalence of acquired as opposed to hereditary activated protein C resistance in the second trimester. Rai et al (2000), also reported a significantly higher incidence of acquired APCR in women with recurrent first trimester and second trimester losses 8.8% (80/904) and 8.7%(18/207), compared to a control group of parous women 3.3%(5/150).…”
Section: Acquired Apcr and Pregnancy Lossmentioning
confidence: 99%
“…In a subgroup of patients with 3 or more pregnancy losses and no successful pregnancies, the prevalence of the mutation was 9% OR 2.6, 95% CI, 1-6.7. Younis et al [108]. evaluated APCR and the FV Leiden mutation in women with first trimester recurrent embryonic loss, in women with second trimester loss and controls.…”
Section: Prevalence Of Inherited Thrombophilias In First and Second Tmentioning
confidence: 99%
“…Multiple studies [14,15,16,17] have shown that thrombophilias increase the risk of recurrent first-and secondtrimester pregnancy losses through placental bed thrombosis. To date, meta-analyses of relatively small case-control studies have demonstrated a small but significant increase (OR 1.5-4.0) in embryonic and fetal loss, abruption, intrauterine growth restriction and preeclampsia in association with inherited thrombophilias [18,19] Prospective cohort studies have similarly supported a minor contribution of inherited thrombophilias on perinatal outcomes [20,21].…”
Section: Introductionmentioning
confidence: 99%